The role of defects in fluorescent silicon carbide layers grown by sublimation epitaxy - Schimmel, Saskia; Kaiser, Michl; Jokubavicius, Valdas; Ou, Yiyu; Hens, Philip; Linnarsson, Margareta K.; Sun, J.; Liljedahl, Rickard; Ou, Haiyan; Syväjärvi, Mikael; Wellmann, Peter (IOP Conference Series: Materials Science and Engineering, 2014)
Donor-acceptor co-doped SiC is a promising light converter for novel monolithic all-semiconductor white LEDs due to its broad-band donor-acceptor pair luminescence and potentially high internal quantum efficiency. Besides sufficiently high doping concentrations in an appropriate ratio yielding short radiative lifetimes, long nonradiative lifetimes are crucial for efficient light conversion. The impact of different types of defects is studied by characterizing fluorescent silicon carbide layers with regard to photoluminescence intensity, homogeneity and efficiency taking into account dislocation density and distribution. Different doping concentrations and variations in gas phase composition and pressure are investigated.
Keywords: SiC; fluorescence; sublimation epitaxy